2022
DOI: 10.48550/arxiv.2201.02594
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Recycled entanglement detection by arbitrarily many sequential and independent pairs of observers

Mahasweta Pandit,
Chirag Srivastava,
Ujjwal Sen

Abstract: We investigate the witnessing of two-qubit entangled states by sequential and independent pairs of observers, with both observers of each pair acting independently on their part of the shared state from spatially separated laboratories, and subsequently passing their qubits to the next pair in the sequence. It has previously been conjectured that not more than one pair of observers can detect Clauser-Horne-Shimony-Holt "Bell-nonlocal" correlations in a similar set-up. This is intriguing since it is possible to… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Sequential detection of Bell nonlocality and bipartite entanglement has been a topic of recent studies [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. It has been shown that there exist states for which Bell nonlocality or entanglement can be detected by arbitrarily many sequential observers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sequential detection of Bell nonlocality and bipartite entanglement has been a topic of recent studies [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. It has been shown that there exist states for which Bell nonlocality or entanglement can be detected by arbitrarily many sequential observers.…”
Section: Discussionmentioning
confidence: 99%
“…The setup is such that one half of the shared bipartite state is controlled by a single observer while the other half is measured and passed on to multiple sequential observers, in order to witness CHSH inequality violation multiple times. In [29][30][31], it is shown that an arbitrary number of observers can sequentially detect Bell nonlocality of shared states and even entanglement of states which are not Bell nonlocal. A number of works have been conducted within this (or slightly generalized [31][32][33]) bipartite scenario [34][35][36][37][38][39][40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…to extract enough information to violate classical limitations, but afterwards preserve enough of the resource to enable further independent quantum information tasks. This includes recycling of quantum communications [2][3][4][5][6][7], entanglement and steering [8][9][10][11][12][13], and perhaps most remarkably nonlocality [14][15][16][17][18][19][20][21]. Using photonic setups, it has been experimentally demonstrated that one share of a singlet state can be recycled to produce two sequential violations of the CHSH inequality [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…to extract enough information to violate classical limitations, but afterwards preserve enough of the resource to enable further independent quantum information tasks. This includes recycling of quantum communications [2][3][4][5][6][7], entanglement and steering [8][9][10][11][12][13], and perhaps most remarkably nonlocality [14][15][16][17][18][19][20][21]. Using photonic setups, it has been experimentally demonstrated that one share of a singlet state can be recycled to produce two sequential violations of the CHSH inequality [22,23].…”
mentioning
confidence: 99%